MULTIFACETED RELATIONAL FORMS IN FRANCHISE ORGANIZATIONS: THE RELATIONAL ROLES OF THE FRANCHISOR BRAND - Ferry Jaolis (Jurnal Manajemen Pemasaran, 2018)
Extant research suggests that consumers use brands to enrich their individual and social lives. By looking at the franchisees beyond the economic rationality perspective, we introduced the brand into the franchise relational analysis and confirmed its impact on their satisfaction and loyalty. Results from the thematic analysis of the qualitative data clearly indicated that the brand supplied franchisees with unique symbolic meanings and hedonic pleasures while aiding them in the development and maintenance of rewarding relationships with multiple stakeholder groups. More importantly, strong franchisee-brand relationship alleviated defects in the franchisor-franchisee relationship. We offered a comprehensive framework of the franchise relationship “package” for future research avenues